MENOPAUSAL HORMONE THERAPY DOES NOT INFLUENCE LUNG CANCER RISK: RESULTS FROM THE CALIFORNIA TEACHERS STUDY - Clague, Jessica (2011)
BACKGROUND: Results from studies examining the association between hormone therapy (HT) and lung cancer risk disagree. METHODS: We examined the associations between HT use and lung cancer risk among 60,592 postmenopausal women enrolled in the prospective California Teachers Study cohort. Between 1995 and 2007, 727 women were diagnosed with lung cancer. Multivariable Cox proportional hazards regression models were fit using age as the time metric. RESULTS: No measure of HT use was associated with lung cancer risk (all p-values for trend≥0.4). In addition, no variations in risk by smoking status (never, ever, former, current), type of HT (E-alone, E+P use), type of menopause, or lung cancer histology were observed. CONCLUSIONS: Our findings do not support an association between HT and lung cancer. IMPACT: This large-scale, prospective study, which capitalizes on the detailed hormone use, smoking history, and type of menopause information available within this unique cohort, was unable to find any association between intake of HT and lung cancer risk.